PENGARUH GAYA KEPEMIMPINAN TRASFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI PADA PT. X - Zahra Rizqiyah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the impact of transformational leadership style and work motivation on employee performance through organizational commitment at PT. X. Employee performance is a key factor in achieving organizational goals, thus requiring leadership that can motivate and develop employees' potential. This research employs a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to employees in the production department of PT. X, with 50 respondents. The data analysis technique used was quantitative analysis. The results show that both transformational leadership style and work motivation have a positive and significant impact on employee performance, both directly and indirectly through organizational commitment. These findings emphasize that organizational commitment plays a mediating role in strengthening the relationship between transformational leadership and work motivation on employee performance.